Voluntary Exercise Promotes Glymphatic Clearance of Amyloid Beta and Reduces the Activation of Astrocytes and Microglia in Aged Mice - He, Xiao-fei; Liu, Dong-xu; Zhang, Qun; Liang, Feng-ying; Dai, Guang-yan; Zeng, Jin-sheng; Pei, Zhong; Xu, Guang-qing; Lan, Yue (Frontiers in Molecular Neuroscience, 2017)
Age is characterized by chronic inflammation, leading to synaptic dysfunction and dementia because the clearance of protein waste is reduced. The clearance of proteins depends partly on the permeation of the blood–brain barrier (BBB) or on the exchange of water and soluble contents between the cerebrospinal fluid and the interstitial fluid (ISF). A wealth of evidence indicates that physical exercise improves memory and cognition in neurodegenerative diseases during aging, such as Alzheimer's disease, but the influence of physical training on glymphatic clearance, BBB permeability, and neuroinflammation remains unclear. In this study, glymphatic clearance and BBB permeability were evaluated in aged mice using in vivo two-photon imaging. The mice performed voluntary wheel running exercise and their water-maze cognition was assessed; the expression of the astrocytic water channel aquaporin 4 (AQP4), astrocyte and microglial activation, and the accumulation of amyloid beta (Aβ) were evaluated with immunofluorescence or an enzyme-linked immunosorbent assay; synaptic function was investigated with Thy1–green fluorescent protein transgenic mice and immunofluorescent staining. Voluntary wheel running significantly improved water-maze cognition in the aged mice, accelerated the efficiency of glymphatic clearance, but which did not affect BBB permeability. The numbers of activated astrocytes and microglia decreased, AQP4 expression increased, and the distribution of astrocytic AQP4 was rearranged. Aβ accumulation decreased, whereas dendrites, dendritic spines, and postsynaptic density protein increased. Our study suggests that voluntary wheel running accelerated glymphatic clearance but not BBB permeation, improved astrocytic AQP4 expression and polarization, attenuated the accumulation of amyloid plaques and neuroinflammation, and ultimately protected mice against synaptic dysfunction and a decline in spatial cognition. These data suggest possible mechanisms for exercise-induced neuroprotection in the aging brain.